Effect of Packing and Storage Behaviour on Shelf Stability of Functionally Enriched Fruit Rolls - Sharma, K. D.; Chandel, Vinay; Gupta, Anil; Verma, Anil K. (International Journal of Economic Plants, 2018)
Storage stability of apple, persimmon, peach and pear fruit rolls prepared by incorporating outer peel of fruits after packing in laminated pouches(150 gauge) and polythene pouches (200 gauge) and storage under refrigerated and ambient temperature was evaluated. The packing of fruit rolls in laminated pouches followed by storage under refrigerated conditions (4-5 oC) upto six months resulting in minimum changes in quality as compared to ambient temperature. During 6 months of storage, an increase in mean moisture content from 13.43 to 15.43% was noticed in polythene pouches whereas, decrease in moisture content from 13.43 to 13.35% was noticed in laminated pouches. After 6 months of storage, ascorbic acid decreased from 14.27 to 13.83, total phenols from 810.12 to 755.24 mg 100 g-1, free radical scavenging activity from 73.10 to 67.18%, total carotenoids from 9.60 to 7.93 mg 100 g-1, and crude fibre contents decreased from 1.75 to 1.38% irrespective of fruit roll type and storage temperature. The packing of fruits rolls in laminated pouches followed by storage at refrigerated conditions is optimized for storage of fruit rolls.